2018
DOI: 10.3390/app8122492
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Impact Rotary–Linear Motor Based on Decomposed Screw-Type Motion of Piezoelectric Actuator

Abstract: A novel impact two-degree-of-freedom (2-DOF) motor based on the decomposed screw-type motion of a piezoelectric actuator (PA) has been proposed. The fabricated prototype motor has a maximum diameter of 15 mm and a length of 100 mm which can produce a maximum torsional angle of about 1000 μrad and a maximum longitudinal displacement of about 1.03 μm under a saw-shaped driving voltage with 720 Vp-p (peak-to-peak driving voltage). When the axial prepressure generated by the spring is about 1N and the radial prepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Unlike rotary to linear ones, direct linear motion actuators have no transmission elements and provide high accuracy, resolution, and speed. There are various types, viz., iron core linear motors, U-channel linear motors, linear shaft motors, voice coil motors, linear motion solenoids, screw-type linear piezoelectric actuators [38], and electromagnetic clutches. The stator and forcer (called rotor), with a permanent magnet and electromagnetic coils, respectively, create linear force.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike rotary to linear ones, direct linear motion actuators have no transmission elements and provide high accuracy, resolution, and speed. There are various types, viz., iron core linear motors, U-channel linear motors, linear shaft motors, voice coil motors, linear motion solenoids, screw-type linear piezoelectric actuators [38], and electromagnetic clutches. The stator and forcer (called rotor), with a permanent magnet and electromagnetic coils, respectively, create linear force.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al reported on the rotary-linear actuator that has a piezoelectric tube with helical electrodes [23]. The actuator operation principle is based on the excitation of the first longitudinal and the first torsional vibration modes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, few dualfunction piezoelectric actuators and motors are proposed [21,22]. However, in most cases, these devices can provide angular and planar motion of the cylinder-shaped slider [23,24]. This paper represents a novel 5-DOF piezoelectric robot that can provide unlimited 2-DOF planar motion and 3-DOF angular motion of the payload independently.…”
Section: Introductionmentioning
confidence: 99%